Vampires, Dragons, and Egyptian Kings : Youth Gangs in Postwar New York. - Schneider, Eric C. (Princeton University Press, 1999)
"They called themselves "Vampires," "Dragons," and "Egyptian Kings." They were divided by race, ethnicity, and neighborhood boundaries, but united by common styles, slang, and codes of honor. They fought - and sometimes killed - to protect and expand their territories. In postwar New York, youth gangs were a colorful and controversial part of the urban landscape, made famous by West Side Story and infamous by the media. This is the first historical study to explore fully the culture of these gangs. Eric Schneider takes us into a world of switchblades and slums, zoot suits and bebop music to explain why youth gangs emerged, how they evolved, and why young men found membership and the violence it involved so attractive." "Schneider focuses on the years from 1940 to 1975, but takes us up to the present in his conclusion, showing how youth gangs are no longer social organizations but economic units tied to the underground economy."--Jacket